Akuntansi Pajak Penghasilan Pasal 22,23,24,25 dan Pajak Penghasilan Final - Lusy Suprajadi (Bina Ekonomi, 2001)
Income tax credit consists of income tax article 21,22,23,24 and 25. In this paper, income tax article 21 is not discussed. Income tax credit which has been paid is classified as prepaid tax, income not as an expense except for final income tax. Final income tax is not included in counting tax liability. Income tax credit accounting is needed to report how much the rest of tax liability must be paid each year.